Analisis Kualitas Kesehatan Kerja dan Pengaruhnya pada Produktivitas Pengrajin Tenun Ikat Tradisional di Dusun Fopo Kelurahan Onatali Kecamatan Rote Tengah Kabupaten Rote Ndao - Jois Seselia Atriesta Seme; Jacob M Ratu; Soleman Landi (Yayasan Literasi Sains Indonesia, 2023)
The quality of health is closely related to occupational safety and health in the workplace, if the quality of work health is good, the work output will increase. The purpose of this study was to describe the level of quality of health seen from the dimensions of fatigue, muscle complaints, dimensions of occupational diseases in the work life of weavers, to analyze the influence between the dimensions of fatigue and the work productivity of weavers, to analyze the influence between the dimensions of muscle complaints and the work productivity of weavers, to analyze the influence between the dimensions of occupational diseases and the work productivity of weavers. The type of research used is analytic correlation with a quantitative approach and a cross sectional design. The number of samples using total sampling is 60 people. Unibivariate and bivariate data analysis using the chi square test. The results of the bivariate analysis showed that there was a relationship between the dimension of fatigue and work productivity p = 0.007, the dimension of muscle complaints p = 0.000, the dimension of work-related illness p = 0.000. Thus the quality of the health of the weavers is not good, so there is a need for socialization regarding the analysis of the health quality of the weaver workers through direct counseling and through various other media. Weavers are also expected to have awareness to pay more attention to their work patterns so that their health can be maintained properly.